Shelving the Coast With Vertipools: Retrofitting Artificial Rock Pools on Coastal Structures as Mitigation for Coastal Squeeze - Hall, Alice E.; Herbert, Roger J. H.; Britton, J. Robert; Boyd, Ian M.; George, Nigel C. (Frontiers in Marine Science, 2019)
Coastal squeeze caused by sea level rise threatens the size, type and quality of intertidal habitats. Along coastlines protected by hard defences, there is a risk that natural rocky shore habitat will be lost, with remaining assemblages characteristic of hard substrata confined to sea walls and breakwaters. These assemblages are likely to be less diverse and different to those found on natural shores as these structures lack features that provide moist refugia required by many organisms at low tide, such as pools and crevices. Engineering solutions can help mitigate the impacts of sea level rise by creating habitats that retain water on existing structures. However, as experimental trials are strongly affected by local conditions and motivations, the development of new techniques and solutions are important to meet the needs of local communities and developers. Following a small scale community project, a feasibility study retrofitted five concrete-cast artificial rock pools (‘Vertipools’) on to a vertical seawall on the south coast of England. After 5 years, the artificial pools increased the species richness of the sea wall and attracted mobile fauna previously absent, including fish and crabs. The Vertipools had assemblages which supported several functional groups including predators and grazers. Although disturbance of algal assemblages on the seawall from the retrofitting process was still evident after 3 years, succession to full canopy cover was underway. Collaboration between policy makers, ecologists, children and artists produced an ecologically sensitive design that delivered substantial benefits for biodiversity and that could be adapted and scaled-up to both mitigate habitat loss and enhance coastal recreational amenity.